Doing theology with children: A childist reading of the childhood metaphor in 1 Corinthians and the Synoptic Gospels - Grobbelaar, Jan (HTS teologiese studies, 2020)
This article is written from the perspective of Child Theology and a childist reading of scripture. Firstly, the article deals with the links between children, childhood and Childhood Studies, as well as with Theology. Secondly, in terms of a childist reading of scripture, it explains the difference between a low and a high view of childhood. The fact that both views of childhood are present in the Bible is highlighted. Thirdly, the article discusses three texts in 1 Corinthians, where Paul used the childhood metaphor in a way that reflects a low view of childhood. Then, it investigates passages from the Synoptic Gospels as examples of Jesus’ implied high view of childhood. Finally, the article concludes with a challenge addressed to all adult theologians.Contribution: This article contributes to the enhancement of emancipatory methodologies for doing theology and research with children by exploring the different ways in which the childhood metaphor is used in 1 Corinthians and the Synoptic Gospels through a childist reading of the relevant texts. Through this hermeneutical approach, which places the article clearly in the scope of this Theological Journal, it is established that doing theology with children in an emancipatory way adult theologians have to operate with a high view of childhood, as expressed in the way the childhood metaphor is used in the Synoptic Gospels.